The role and impact of e-commerce to small and medium industries in Malaysia / Mohamad Azmi Nias Ahmad - Ahmad, Mohamad Azmi Nias (Universiti Teknologi MARA Cawangan Pahang, 2003)
After the recession period in the year 1997 to 1998, and after the collapse of many big companies in Malaysia, the Small and Medium Industries (SMI) come into the picture in order to bounce back. E-Commerce is another strategy that Malaysian SMI could use in order to become more competitive with their business rivals, to compete globally and to be integral part of the Malaysian industrial development and hope to helps economic growth of the nation.